(untitled) (Journal of the College of Basic Education, 2025)
Introspection is one of the most important sources of revealing personal feelings, and one of the methods that the poet resorts to to reveal the feelings hidden deep within him. Through this introspection process, he does not stray far from what the patient tells the doctor about his suffering and pain, to guide him to diagnosis and follow-up. He is frightened by introspections that are not fleeting, but rather deeply rooted in the soul, and cannot be forgotten until he feels nothingness, which is a truly difficult equation between existence and non-existence. The choice fell on the poet Al-Malik Al-Amjad, who was distinguished by his artistic and realistic awareness, in addition to the clarity of the artistic and intellectual goals behind the introspection process that he is carrying out. He stands before the problem of depicting his emotional state, studying it, and presenting its data. This requires the deepest types of thinking to comprehend the self and encompass its worlds to enable him to conduct the correct introspection process. Hence, the choice was made for this type of study and for the poet Al-Malik Al-Amjad in particular. Among these previous studies that I have reviewed is a study entitled (Self-Introspection and the Search for Myth, a Critical Study of the Diriyyat of Abu al-Ala al-Ma’arri) by researcher Camelia Abdel Fattah, which is far from the content of this study. What I would like to mention is the scarcity of studies in this field, so it was necessary for us to double our efforts to reach everything that would feed and support this study. Among the sources that I benefited from is the study (Introspection in Psychology: From the Origins to the Laboratory) by researchers Muwaffaq Krum and Sarir Ahmad bin Musa, and a study entitled (Manifestations of Self-Introspection in the Poetry of Kamal Nasser) by researcher Ibrahim Nimr Musa. I do not claim to have encompassed knowledge of everything related to the details of this study, but it is enough for me that I have worked hard in a study that I saw as unprecedented. The difficulties of research and its components are not hidden, especially the scarcity of its sources.